TEKNOLOGI PENGOLAHAN MINYAK KELAPA DAN HASIL IKUTANNYA / Processing Technology of Coconut Oil and Its By Products - Steivie Karouw; Budi Santosa; Ismail Maskromo (Jurnal Penelitian dan Pengembangan Pertanian, 2019)
Coconut is one of the plantations spread in almost all regions of Indonesia. Farmers generally processed coconut into primary products in the form of copra and dehusked coconut. The prices of these two products continue to fluctuate. The efforts that can be made to increase income from farming of this commodity are to encourage farmers to diversify the products by processing some valuable products. Integrated coconut processing on a farmer group scale can be a way to increase farmers’ earning. This paperdescribes the technology of processing coconut oil and its by products, the quality of the products and utilization, and the development opportunities. The technology for processing some products from coconut meat and its by-products are available and can be applied at the farm level. Products that can be made in the form of food products are VCO, healthy cooking oil, nata de coco, coconut flour and non-food products like animal feed, organic fertilizer and biodiesel. The obtained VCO and coconut oil quality are according with the Indonesian National Standard (SNI). Both of these oils contain medium chain fatty acids which are dominated by lauric acid, so they can be consumed directly and as cooking oil. Another product is nata de coco which can be consumed directly. Coconut residue contains high dietary fiber as a substitute for wheat flour. The coconut residue can also be processed into high protein feed. Coir dust is fermented into organic fertilizer and waste oil through the transesterification process into biodiesel as an environmentally friendly fuel to substitute diesel.Keywords: coconut, processing, oil, by product AbstrakKelapa merupakan salah satu tanaman perkebunan yang tersebar di hampir semua wilayah Indonesia. Petani umumnya mengolah buah kelapa menjadi produk primer berupa kopra dan kelapa butiran. Harga kedua produk tersebut berfluktuasi. Usaha yang dapat dilakukan untuk meningkatkan pendapatan dari usahatani komoditas ini ialah mendorong petani melakukan diversifikasi produk olahan kelapa. Pengolahan kelapa secara terpadu dalam skala kelompok tani dapat menjadi jalan keluar untuk meningkatkan pendapatan. Tulisan ini mendeskripsikan teknologi proses pengolahan minyak kelapa dan hasil ikutannya, mutu produk yang dihasilkan dan pemanfaatannya, serta peluang pengembangan. Teknologi pengolahan produk dari daging buah kelapa dan hasil ikutannya telah tersedia dan dapat diaplikasikan di tingkat petani. Produk yang dapat dihasilkan dalam bentuk bahan pangan ialah berupa minyak kelapa dalam bentuk VCO dan minyak goreng sehat, nata de coco, tepung ampas kelapa serta produk nonpangan berupa pakan ternak, pupuk organik, dan biodiesel. Produk VCO dan minyak kelapa memiliki mutu yang sesuai dengan Standar Nasional Indonesia (SNI), mengandung asam lemak rantai medium yang didominasi oleh asam laurat, sehingga dapat dikonsumsi langsung dan sebagai minyak goreng. Produk lainnya yaitu nata de coco yang dapat langsung dikonsumsi. Tepung ampas kelapa mengandung dietary fiber tinggi sebagai substitusi tepung gandum. Selain diolah menjadi tepung, ampas kelapa juga dapat diproses menjadi pakan berprotein tinggi. Debu sabut dapat difermentasi menjadi pupuk organik dan minyak jelantah melalui proses transesterifikasi menjadi biodiesel sebagai bahan bakar ramah lingkungan pengganti solar.Kata kunci: Kelapa, pengolahan, minyak, produk ikutan